184k views
5 votes
Solve for x.

7 - (2x + 11) + 3(3 - x) = 20

7/5
-3
-4

User John Kary
by
5.5k points

1 Answer

3 votes

Answer:

x = -3

Explanation:

You will have to distribute first

7 -2x -11 + 9 -3x = 20

Then, combine you like terms

-2x -3x = -5x

7 -11 +9 =5

Then you write it as an equation

-5x +5 = 20

Next you will want to have x by itself which means you have to get rid of the 5 by substracting 5 on each side (opposite of addition is substraction)

-5x = 15

Then you divide each side by -5 ( opposite of multiplication is division)

x= -3

Hope this helped :D

User Paolo Tagliaferri
by
5.5k points